The Role of 6-Minute Walk Test Guided by Impedance Cardiography in the Rehabilitation Following Knee Arthroplasty: A Randomized Controlled Trial - Lin, Yangyang; Hu, Xingwei; Cao, Yalin; Wang, Xing; Tong, Yao; Yao, Fengjuan; Wu, Peihui; Huang, Huiling (Frontiers in Cardiovascular Medicine, 2021)
Objective: To explore the effect of six-minute walk test (6MWT) guided by non-invasive cardiac output on the rehabilitation of patients with knee osteoarthritis following artificial total knee arthroplasty. Methods: Sixty-six patients with knee osteoarthritis planned to undergo artificial total knee arthroplasty were included from March 2019 to October 2019, and randomly assigned to intervention group or control group. Under the guidance of clinical rehabilitation physician, orthopedic physician, and cardiologist, a home rehabilitation exercise program based on 6MWT and non-invasive cardiac output was formulated for patients with knee osteoarthritis. The participants of intervention group conducted full rehabilitation training supervision and guidance through the WeChat platform to ensure their rehabilitation trainings were completed safely and effectively. AS for the control group, patients were just given rehabilitation training manuals at the time of discharge, and completed the training by themselves. Results: At 6 months postoperatively, six-minute walk distance (6MWD 413.88±44.61 vs. 375.00±40.53 meters, P<0.05), active metabolic equivalent (METS 4.13±0.29 vs 3.88±0.27, P<0.05), stroke volume after 6MWT (SV 114.97±12.05 vs 98.38±16.43ml, P<0.05), cardiac output (CO 11.92±1.68 vs 9.79±1.82L/min, P<0.05) of the intervention group were significantly higher than those of the control group. The symptom evaluation scores of intervention group were also better than those of the control group. Conclusions: The multidisciplinary postoperative rehabilitation exercise training program is beneficial to the recovery of lower limb function and the improvement of exercise capacity after knee replacement, and it also helps to improve the non-invasive hemodynamic indicators related to the patient's cardiac function.